Survey of pesticides in chicken carcasses and environments of backyard raising system in rural area of Thailand - Natnaree Rakarkaraphokhin; Montira Intanon; Nattakarn Awaiwanont; Warangkhana Chaisowwong (Veterinary Integrative Sciences)
This study consists of a survey of pesticides in chicken carcasses in the environment of backyard raising systems in rural areas of Thailand, focusing on Mae Taeng District, Chiang Mai Province. It aims to survey organophosphate and carbamate pesticides in soil, water, chicken muscle, and liver samples while assessing the knowledge and behaviors related to pesticide use and backyard chicken rearing. Among 377 farmer households surveyed, 94% displayed high pesticide knowledge, but moderate pesticide usage and irresponsible practices were noted in equipment management and waste disposal. The age of the chicken raiser correlated significantly with pesticide knowledge (p<0.05), suggesting older individuals possess greater understanding due to their accumulated experience and education. Environmental samples (soil and water) and chicken samples (muscle and liver) were collected. No organophosphate or carbamate pesticides were detected in the water, chicken muscle, or liver samples. However, soil samples from the Sop Ping Subdistrict tested positive for these pesticides when screened using the GT-Pesticide Test Kit. The High-Performance Liquid Chromatography (HPLC) analysis confirmed that there were non-detectable pesticides in all samples. Further research is required to identify alternative pesticides and examine the quantity in depth to overcome the behavioral barriers to effective pesticide use in chicken rearing. Promoting a positive attitude toward knowledge and practice for achieving sustainable pest management is crucial for farmer well-being and environmental health.